2018
DOI: 10.1111/scs.12558
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration among eldercare workers: barriers, facilitators and supporting processes

Abstract: To retain qualified care workers and to ensure high-quality care for residents in eldercare homes, well-functioning collaboration among care workers is pivotal. This study aims to identify barriers and facilitators of collaboration among eldercare workers and to describe the processes leading to well-functioning collaboration. We collected focus group data from 33 eldercare workers from seven Danish eldercare homes. We found that collaboration was hampered by a number of formal and informal divisions among car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Findings have supported this aspect of the theory in airlines, in early intervention agencies and in health care (Bright, 2012;Derrington, 2012;Gittell, 2001). More broadly, relational approaches to leadership were positively were positively associated with relational coordination in child care , elder care (Jakobsen et al, 2018), education (Van Rooyen, 2018), and construction (Hellenes & Thrap-Meyer, 2017). In addition, nurse representation in top leadership roles was positively associated with relational coordination across health care professions (Mark et al, 2007).…”
Section: Relational Leadership Rolesmentioning
confidence: 85%
See 3 more Smart Citations
“…Findings have supported this aspect of the theory in airlines, in early intervention agencies and in health care (Bright, 2012;Derrington, 2012;Gittell, 2001). More broadly, relational approaches to leadership were positively were positively associated with relational coordination in child care , elder care (Jakobsen et al, 2018), education (Van Rooyen, 2018), and construction (Hellenes & Thrap-Meyer, 2017). In addition, nurse representation in top leadership roles was positively associated with relational coordination across health care professions (Mark et al, 2007).…”
Section: Relational Leadership Rolesmentioning
confidence: 85%
“…While few studies have been conducted thus far, the findings have been consistent. In airlines (Gittell, 2000), surgical care (Gittell et al, 2010), and elder care (Jakobsen et al, 2018), proactive horizontal conflict resolution was found to be positively associated with relational coordination across roles. Exploring the reverse causal path, a study of hospital care found that relational coordination was associated with fewer conflicts between employees and managers and with fewer strikes (Ekwueme, 2018).…”
Section: Conflict Resolutionmentioning
confidence: 96%
See 2 more Smart Citations
“…The contextual factors that adversely affect nurses' willingness to remain in their positions must be eliminated. This approach will support healthcare workers' commitment and engagement in their careers [27], which have been suggested, along with enhanced satisfaction and motivation, to significantly bolster the retention of nurses in healthcare settings and prevent a dearth of talent [28].…”
Section: Discussionmentioning
confidence: 99%